QTL identification for tolerance to fruit set in tomato by FAFLP markers - Grilli, Gisele Ventura Garcia; Braz, Leila Trevizan [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP] (My University, 2007)
This study aimed to detect quantitative trait loci (QTL) by fALP (Fluorescent Amplified Fragment Length Polymorphism) markers associated to the trait tomato fruit set at high temperatures. A biparental cross between line Jab-95 (heat-tolerant) and cultivar Caribe (heat-susceptible) was made. A total of 192 plants of the F2 generation were evaluated, generating 172 polymorphic markers through six primer combinations previously identified by the Bulked Segregant Analysis technique. To construct the genetic map, 106 of the 172 markers that segregated in the expected Mendelian segregation proportion (3:1) were used. The map covered 1191.46 cM of the genome. Six trait-linked QTL were identified in the analysis of simple markers and three others by the interval-mapping methodology. These results could be highly useful in improvement programs, since heat-tolerant plants can be selected rapidly, which improves tomato fruit set.
Keywords: fAFLP; Linkage map; Lycopersicon esculentum; Molecular markers; Stress